2013
DOI: 10.2337/db11-1116
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End Products Regulates Adipocyte Hypertrophy and Insulin Sensitivity in Mice

Abstract: Receptor for advanced glycation end products (RAGE) has been shown to be involved in adiposity as well as atherosclerosis even in nondiabetic conditions. In this study, we examined mechanisms underlying how RAGE regulates adiposity and insulin sensitivity. RAGE overexpression in 3T3-L1 preadipocytes using adenoviral gene transfer accelerated adipocyte hypertrophy, whereas inhibitions of RAGE by small interfering RNA significantly decrease adipocyte hypertrophy. Furthermore, double knockdown of high mobility gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 53 publications
6
85
0
1
Order By: Relevance
“…In ApoE/RAGE double knockout mice, it was demonstrated that RAGE regulated adiposity. Monden et al 28 demonstrated that an increase in body weight induced by high-fat diet is suppressed in RAGE knockout mice. In contrast to these studies, we did not observe an effect of RAGE on adiposity in the Leptr Db-/-background.…”
Section: /Leptrmentioning
confidence: 99%
See 4 more Smart Citations
“…In ApoE/RAGE double knockout mice, it was demonstrated that RAGE regulated adiposity. Monden et al 28 demonstrated that an increase in body weight induced by high-fat diet is suppressed in RAGE knockout mice. In contrast to these studies, we did not observe an effect of RAGE on adiposity in the Leptr Db-/-background.…”
Section: /Leptrmentioning
confidence: 99%
“…Previous research has also demonstrated that RAGE deficiency significantly decreased the expression of proinflammatory mediators and lower levels of oxidative stress, whereas adiponectin levels and antioxidative defense mechanisms were higher in RAGE-deficient mice. [24][25][26][27][28] In addition, the favorable effect of RAGE deficiency on insulin sensitivity and glucose metabolism was also demonstrated in RAGE knockout mice fed a high-fat diet. 27,28 RAGE deficiency was also associated with higher glucose transporter-4 expression in adipose tissue in these mice.…”
Section: /Leptrmentioning
confidence: 99%
See 3 more Smart Citations